'Moving life stories tell us just why politics matters’: personal narratives in tabloid anti-austerity campaigns - Birks, Jen (SAGE, 2016)
This article examines the use of personal narratives in two tabloid newspaper campaigns against a controversial welfare reform popularly known as the ‘bedroom tax’. It aims firstly to evaluate whether the personal narratives operate as political testimony to challenge government accounts of welfare reform and dominant stereotypes of benefits claimants, and secondly to assess the potential for and limits to progressive advocacy in popular journalism. The study uses content analysis of 473 articles over the course of a year in the Daily Mirror and Sunday People newspapers, and qualitative analysis of a sub-set of 113 articles to analyse the extent to which the campaign articles extrapolated from the personal to the general, and the role of ‘victim-witnesses’ in articulating their own subjectivity and political agency. The analysis indicates that both newspapers allowed affected individuals to express their own subjectivity to challenge stereotypes, but it was civil society organisations and opinion columnists who most explicitly extrapolated from the personal to the political. Collectively organised benefits claimants were rarely quoted, and there was some evidence of ventriloquization of the editorial voice in the political criticisms of victim-witnesses. However, a campaigning columnist in the Mirror more actively empowered some of those affected to speak directly to politicians. This indicates the value of campaigning journalism when it is truly engaged in solidarity with those affected, rather than instrumentalising victim-witnesses to further the newspapers’ campaign goals.